Lectotype designation, redescription, and synonymy of Homonyx cupreus Guérin-Méneville, 1839 (Coleoptera: Scarabaeidae: Rutelinae: Rutelini) - Mondaca, José (Zootaxa, 2022)
A syntype of Homonyx cupreus Guérin-Méneville, 1839 (Coleoptera: Scarabaeidae: Rutelinae: Rutelini) was located, studied, and designated a lectotype. As the original description lacking adequate diagnostic characters, the species is redescribed based on the lectotype and on specimens of Homonyx collected in Brazil that are conspecific with H. cupreus. Diagnostic characters and photographs of the type and non-type specimens are presented, and its true distribution in South America is established. Based on morphology and examination of type specimens, Homonyx chalceus bahianus Ohaus, 1913 is a new junior synonym of Homonyx cupreus.